2011
DOI: 10.1007/s10620-010-1558-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Enhanced Cytoprotective Function of HSP90-Overexpressing Small Intestinal Epithelial Cells

Abstract: Our results suggest that HSP90 might play an important role in protecting small intestinal epithelial cells from hydrogen peroxide-induced or indomethacin-induced cell injury in vitro, and raised the possibility of protection of small intestinal epithelial cells by manipulation of HSP90 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…18 Some previous animal studies indicate that HSP90 may have a dual role and increase inflammation in some conditions, while being protective and down-regulating inflammation in other conditions. [19][20][21] Fatigue has previously been an overlooked and ignored phenomenon in IBD but is increasingly recognised as one of the major problems for many patients. Clinically significant fatigue affects roughly 50% of patients at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…18 Some previous animal studies indicate that HSP90 may have a dual role and increase inflammation in some conditions, while being protective and down-regulating inflammation in other conditions. [19][20][21] Fatigue has previously been an overlooked and ignored phenomenon in IBD but is increasingly recognised as one of the major problems for many patients. Clinically significant fatigue affects roughly 50% of patients at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…HSP90 is another general cytosolic chaperone orchestrating the folding of many proteins including structural proteins and inducible proteins. However, HSP90 alone is insufficient to assist the refolding of partially denatured proteins and requires other chaperones, such as HSP70, to complete this task [36,37]. A decrease in the expression of HSP70 was sometimes detected in the proximal and midbody wall muscle tissues of animals exposed to heavy metals [38].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that elevation of Hsp70 in heart provided protection against stress-induced myocardial injury. Additionally, Hsp90 and Hsp60 might play an important role in protecting small intestinal epithelial and mucosal cells from hydrogen peroxide-induced or indomethacin-induced cell injury (Takada et al 2010;Tamaki et al 2011). The variations of Hsp27 expression are associated with strengthening of the cytoskeleton and an increased tolerance of the cell to injury induced by stress (Guay et al 1997).…”
Section: Discussionmentioning
confidence: 99%